(untitled) (Simbiótica. Revista Eletrônica, 2025)
As the opening text of the dossier New Rights, Youth, and Disputes over Subjectivity in Latin American Education, we present a synthesis of research on sociopolitical and educational transformations in Latin America. To this end, the text contextualizes contemporary theoretical and empirical contributions on these topics and presents the articles compiled in this issue of the Simbiótica Journal. These articles focus on the convergence of neoliberal and neoconservative logics with digital information regimes, dynamics catalyzed by the COVID-19 crisis. Thus, a scenario of weakening systemic integration and partisan atomization is described, framing the emergence of the fourth wave of the far right. Based on evidence gathered from cases in Argentina, Brazil, and Peru, the presentation highlights that the works refute the perception of youth political apathy. On the contrary, they reveal a youthful protagonism characterized by a networked “cultural battle” that contests meanings within institutions and social networks. Finally, the paper introduces the problem of how these platforms shape subjectivities by promoting individualistic and meritocratic positions